(untitled) - Pinki Kumari; Aman Kumar; Sanjeev Kumar (Asian Journal of Medical Research, 2019)
Background: Sex determination isutmost importantfor forensic experts and Anthropological studies.Aim: The aim of  this  study  is  to compare cranial morphology between male and  female  skull using MAP Triangle.Subjects and Methods:A total of 100 adult dry skull (50male and 50 female) were used for study using a digitalVerniercalliper. Results:The male parameters were significantly higher then female parameters with no significance difference in Right and Left side of male and female.Conclusion: The skull is most commonly site for sexual dimorphisms in human Skeleton and MAP Triangle can be additive value gender differentiation.